Pẽptykre Parkatêjê School: dialogued knowledge from the Gavião paintings - Queiroz, Elizete de Lima; Ribeiro Júnior, Ribamar (ODEERE, 2022)
This work is part of the research that has been carried out from a look at the daily life of the Indigenous State School of Early Childhood, Elementary and Middle Education Pẽptykre Parkatêjê, it aims to bring the curricular experience of this school articulated with the dynamics of the Parkatêjê people who inhabit the Mãe Maria Indigenous Land, in the municipality of Bom Jesus do Tocantins, in an area that we call the Gavião ethnoterritory. In this sense, the work brings reflections and analysis of the methodology developed in the curriculum in motion, as well as in the actions that are triggered throughout the year through the ceremonial calendar of the village.